The R package EchoviewR for automated processing of active acoustic data using Echoview - Harrison, Lisa-Marie K.; Cox, Martin J.; Skaret, Georg; Harcourt, Robert (Frontiers in Marine Science, 2015)
Acoustic data is time consuming to process due to the large data size and the requirement to often undertake some data processing steps manually. Manual processing may introduce subjective, irreproducible decisions into the data processing work flow, reducing consistency in processing between surveys. We introduce the R package EchoviewR as an interface between R and Echoview, a commercially available acoustic processing software package. EchoviewR allows for automation of Echoview using scripting which can drastically reduce the manual work required when processing acoustic surveys. This package plays an important role in reducing subjectivity in acoustic data processing by allowing exactly the same process to be applied automatically to multiple surveys and documenting where subjective decisions have been made. Using data from a survey of Antarctic krill, we provide two examples of using EchoviewR: krill biomass estimation and swarm detection.